Transformation of Tourist Villages into Wellness Destinations Based on Community Participation and Digital Innovation - Susanti, Putu Herny; Susi Indriyani; Rahmawati, Rahmawati; Kraugusteeliana, Kraugusteeliana (International Journal of Community Service (IJCS), 2025)
Kenderan Village in Gianyar Regency, Bali, has great potential as a wellness tourism destination based on local wisdom. The natural beauty, spiritual culture, and traditional practices such as yoga, meditation, and herbal medicine make this village an ideal location for physical, mental, and spiritual health tourism. However, the management of wellness tourism still faces challenges, such as limited digital marketing, lack of tourism management skills, and minimal supporting infrastructure. This Community Service (PKM) activity aims to increase the capacity of the community to manage wellness tourism professionally and sustainably through a participatory approach and digital innovation. This program includes training in digital marketing, branding strategies, homestay management, and the use of digital technology in tourism promotion. In addition, collaboration with academics, government, and wellness practitioners is strengthened to build a community-based tourism ecosystem in Kenderan Village. The results of the program show an increase in community skills in digital marketing and destination management, which contributes to increasing the village's visibility at the national and international levels. The implementation of digital platforms, such as village websites and social media, has succeeded in attracting more wellness tourists. In addition, community participation has increased with the formation of wellness business groups, such as homestay healing, herbal medicine production, and traditional therapy. However, challenges remain, including improving digital and physical infrastructure, certifying wellness instructors, and strengthening the global wellness community network. Long-term strategies such as continued mentoring, private sector collaboration, and replication of this development model in other tourism villages are needed. With the right approach, Kenderan Village has the potential to become a leading wellness tourism destination in Bali, which not only improves community welfare but also provides an authentic healing experience for global tourists.